EGFR Exon 19 Deletion is Associated With Favorable Overall Survival After First-line Gefitinib Therapy in Advanced Non–Small Cell Lung Cancer Patients. (April 2018) - Choi, Yong Won; Jeon, So Yeon; Jeong, Geum Sook; Lee, Hyun Woo; Jeong, Seong Hyun; Kang, Seok Yun; Park, Joon Seong; Choi, Jin-Hyuk; Koh, Young Wha; Han, Jae Ho; Sheen, Seung Soo
Abstract : Objectives: Exon 19 deletion and L858R mutation in exon 21 of the epidermal growth factor receptor (EGFR) are both common mutations that predict a good response to EGFR tyrosine kinase inhibitors in non–small cell lung cancer (NSCLC). However, the existence of clinically significant difference in sensitivity to EGFR tyrosine kinase inhibitors among different EGFR mutation subtypes is still a matter of debate. Materials and Methods: The outcome of 60 EGFR mutation-positive advanced NSCLC patients who received first-line gefitinib therapy (250 mg/d) was retrospectively analyzed according to EGFR mutation subtypes. Results: The median progression-free survival (PFS) and overall survival (OS) after the initiation of gefitinib therapy for all patients was 11 and 26 months, respectively. Univariate analysis showed that patients with exon 19 deletion (n=28) had significantly longer median PFS (20 vs. 8 mo, P =0.004) and OS (36 vs. 22 mo, P =0.001) compared with those with L858R mutation (n=25) and uncommon or dual mutations (n=7). Multivariate analysis revealed that exon 19 deletion ( P =0.007) was an independent prognostic factor of favorable PFS, with an independent association with poor PFS of male sex ( P =0.049). Exon 19 deletion was also independently associated with favorable OS ( P <0.0001), whereas male sex ( P =0.004) and primary metastatic disease ( P =0.032) were independent prognostic factors of poor OS. Conclusions: The EGFR exon 19 deletion was associated with favorable PFS and OS in patients receiving first-line gefitinib treatment. The EGFR mutation subtype should be considered when making treatment decision or designing clinical trials for chemotherapy-naive, EGFR mutation-positive advanced NSCLC patients.